New bid-ask spread estimators from daily high and low prices - Li, Zhiyong; Lambe, Brendan; Adegbite, Emmanuel (Elsevier, 2018)
Estimating trading costs in the absence of recorded data is a problem that continues to puzzle financial market researchers. We address this challenge by introducing two low frequency bid-ask spread estimators using daily high and low transaction prices.